(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The essay deals with the case of pro-life associations which bury aborted fetuses even if parents do not give directives in this sense. The analysis focuses particularly on the few provisions in the mortuary regulations with the aim to illustrate how the parent does not have the power to prohibit the burial of his or her own fetus, because this can be requested by anyone.